Short communication: Inhibitory activities of the lantibiotic nisin combined with phenolic compounds against Staphylococcus aureus and Listeria monocytogenes in cow milk - Alves, Fernanda C. B. [UNESP]; Barbosa, Lidiane N. [UNESP]; Andrade, Bruna F. M. T. [UNESP]; Albano, Mariana [UNESP]; Furtado, Fabiana Barcelos [UNESP]; Marques Pereira, Ana Flavia [UNESP]; Rall, Vera L. M. [UNESP]; Fernandes Junior, Ary [UNESP] (Elsevier B.V., 2016)
We aimed to investigate the antibacterial activities of carvacrol, thymol, eugenol, cinnamaldehyde, and lantibiotic nisin against standard bacterial strains of the milk pathogens Staphylococcus aureus ATCC 25923 and Listeria monocytogenes ATCC 15313 in cow milk. The minimum inhibitory concentrations (MIC) of these substances were recorded. The synergistic effects were also assessed in culture medium (time kill curve) and in a food model (cow milk) during the storage period (4 degrees C for 6 d) after inoculation with S. aureus and L. monocytogenes individually by combining nisin and the phenolic compounds at proportions of 1/4 + 1/4 the MIC (determined in a previous in vitro assay) in the culture medium and 1/4 + 1/4 of MIC in the food model. Inhibitory activities of nisin and the tested compounds, as well as synergism in the combinations, were found against both bacteria assayed. Bacteriostatic effects were found with all combinations and a significant difference in L. monocytogenes reduction was found compared with the control assays. Thus, the antibacterial activity of nisin combined with phenolic compounds was confirmed against these pathogenic bacteria that are important in the milk industry, or more broadly in food science, with potential applications for milk preservation.
Keywords: nisin; phenolic compounds; synergism antimicrobial; milk pathogen